Rapid population sex‐ratio changes in the moss Ceratodon purpureus. Issue 7 (23rd July 2018) - Eppley, Sarah M.; Rosenstiel, Todd N.; Chmielewski, Matthew W.; Woll, S. Cody; Shaw, Zoë M.; Shortlidge, Erin E.
Abstract : Premise of the Study: Sex‐ratio variation occurs widely in dioecious plants, but the mechanisms of population sex‐ratio bias are poorly understood. In bryophytes, sex ratios are often female biased, and little information is available about how and when bias forms. Methods: To test whether population sex‐ratio variation can emerge during the gametophytic phase and is not purely a product of spore sex ratios, we created artificial populations of the moss Ceratodon purpureus, with male‐ and female‐biased sex ratios, and placed half under a stress treatment. We hypothesized that male‐majority populations would become female‐biased and that stress would increase this transition. After 18 mo, when sporophytes were initially forming, we used sex‐specific molecular markers to determine population sex ratios. Key Results: Female‐majority populations did not differ significantly from their original bias, whereas male‐majority populations became significantly more female biased. The plants had only just produced their first spores, so these sex‐ratio changes occurred during the gametophytic generation, as a result of sex‐specific growth or survival. Sporophytes occurred only in populations with female‐biased final sex ratios, which suggests that females in male‐majority populations may have invested energy in ramets rather than in sporophyte production. The stress treatment was mild and had no effect on sex ratio. Conclusions: Our results suggest that female bias can be generated during the gametophytic generation, before plants reach sexual maturity. These results, combined with those of previous work, suggest that both the gametophytic and the sporophytic stages drive population sex ratios in C. purpureus, thus indicating that multiple mechanisms operate to create biased population sex ratios.